The way from dusty death: Turner and Newall and the regulation of occupational health in the British asbestos industry 1890s-1970 - Bartrip, Peter (London, 2001)
"This study explores the regulation of occupational health in the British asbestos industry from the recognition in the late 1890s that asbestos dust might pose a health hazard until the establishment of the 1969 Asbestos regulations. Whereas almost all of those who have written on this subject have attacked the entire asbestos industry and all its works, The Way from Dusty Death takes a more balanced view. It accepts the history of asbestos and health as in many ways a human tragedy, but it rejects simplistic, universalised arguments that this has been a tragedy with a cast only of villains, dupes and victims. The historical account includes the emergence of medical, and then official, concern about the three diseases related to asbestos (asbestosis, lung cancer and mesothelioma) the legislative process during and after the 1930s and the impact of the 1931 Asbestos Industry Regulations. The book brings together much previously unexamined material - including copious government records, combined with unimpeded access to the vast archive of documents kept by the leading British asbestos manufacturer, Turner and Newall - to present a unique analysis of occupational health and its regulation in the 20th Century."